Efektifitas Ekstrak Etanol Kelopak Buah Sonneratia alba sebagai Larvasida Aedes aegypti - Ratna Yuliawati; Deny Kurniawan; Indah Permata Sari (Sanitasi: Jurnal Kesehatan Lingkungan, 2017)
Sonneratia alba is a mangrove species that is widely found in Indonesia. Phytochemicals studies on Sonneratia alba showed that this plant is very potential as an anti-fungal and larvacide, es-pecially found in the bark. However, there are only few studies on the utilization of the fruit of Sonneratia alba. Therefore, study of the phytochemicals of the fruit petals of Sonneratia alba that might be useful as a larvacide, is needed. Process of this research was an extraction of fruit pe-tals with using ethanol, and the result was then phytochemically tested in order to know the con-tained active compounds. Subsequently, the extract was tested for its effectiveness as larvicide by using instar III/IV of Aedes aegypti larvae as the tested insect, at five concentrations, i.e. 500 ppm, 1000 ppm, 2000 ppm, 3000 ppm, and 4000 ppm. Based on the phytochemical screening, it is known that the ethanol extract of Sonneratia alba fruit petals contain flavonoid and carbohy-drate. The larvacide test results show that the extract is effective for killing Aedes aegypti larvae at 3000 ppm and 4000 ppm concentrations, because both yields ? 50 % mortality.